Hypoalbuminemia in COVID-19 Patients: A Predictor of Disease Severity and Guarded Outcome - Nayab Gull, Bushra Arif, Tahira Bibi, Fahad Ullah Mahmood, Muneeba Ahmed, Iqra Anwaar, M. Husnaian Murtaza, Sitara Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pandemic of COVID-19 is spreading in all continents. There have been lots of article published on different aspects of this infection. Finding low Albumin levels in the patients of COVID-19 disease regardless of their degree of severity of infection has surprised us from the beginning. Aim: To review the hypoalbuminemia and its extent in local population presented with COVID-19 and to determine the relationship of degree of hypoalbuminemia with the severity of infection. Place and duration of study: Bahria International Hospital Lahore and Services Institute of Medical Sciences, Lahore from 1st May 2021 to 30th September 2021. Methodology: Medical records 400 COVID-19 patient’s related symptoms such as cough, flu, fever, headache, tiredness, distress in breathing were included. Serum Albumin, AST and ALT as clinical bioindicators in COVID-19 patients were reviewed. Results: A significant decrease in serum albumin levels with the means and standard deviation (2.692±0.302), (χ²=344.69, df=16, p<0.001) was recorded. Whereas, a significant increase AST (U/L) and ALT (U/L) with the means and standard deviations (45.130±31.138), (χ²=214.30, df=72, p<0.001) was also noted. Analysis between survivors and non-survivors shows the level of albumin and AST/ALT was inversely proportional. Conclusion: Low albumin is associated with disease severity and poor outcomes in terms of prolonged admissions and worse respiratory failure due to alveolar endothelial damage in COVID-19.